STRATEGI DISTRIBUSI PRODUK TEH SIAP SAJI - Sally Wiedjarnarko; Anas Miftah Fauzi; Meika Syahbana Rusli (Jurnal Manajemen & Agribisnis, 2015)
Freshbrew Mels Beverages is a small-sized packaged tea beverage company. The brand product is "Mary Tea" which consists of two types of tea beverages. The company uses forwarding channel in delivering its products to the markets in Central Java, Lampung and Bali. The current problems faced by the company include the channel distribution which is not optimum in delivering its total products and costs it has spent. This study was designed to analyze the optimum distribution system and formulate the most cost-effective product delivery strategy.  The methods used were descriptive and quantitative approaches. The descriptive method included a method of benchmarking, and the quantitative approach included analysis of the distribution margin, Data Envelopment Analysis (DEA), Analytic Hierarchy Process (AHP), and financial analysis. The results show that: 1) a forwarder was the only distribution system used by the company, 2) Central Java was ‘under-performing group’, whereas Lampung and Bali were in ‘effectively managed but sales’ group, 3) the critical factor that affected the highest distribution costs was the number of authorized distributors owned by the company, 4) the best alternative strategy was to expand sales locations in the area of production, and 5) the investment for purchasing a container truck in order to minimize cost was feasible with NET B/C of 4.88 for 5 years and 6 months. The recommended strategies for solving the problem include developing markets, selecting transportation and expedition, having authorized distributors, increasing sales, and creating coordinated management system. Keywords: distribution, distribution margin, DEA, AHP, financial analysisABSTRAKFreshbrew Mels Beverages adalah sebuah perusahaan yang bergerak di bidang minuman ringan yang memproduksi teh dalam kemasan. Merek produknya adalah “Mary Tea” yang terdiri dari dua jenis minuman teh. Freshbrew Mels Beverages menggunakan sistem distribusi “forwarder” dalam mendistribusikan produk ke pasaran yaitu Jawa Tengah, Lampung dan Bali. Permasalahan yang dihadapi oleh perusahaan adalah saluran distribusi yang tidak optimal dalam jumlah produk yang dikirimkan dan biaya yang dikeluarkan. Tujuan dari penelitian ini adalah menganalisis sistem distribusi yang digunakan oleh perusahaan dan merumuskan strategi untuk mendistribusikan produk dengan biaya minimum. Metode yang digunakan adalah metode deskriptif dengan pendekatan kuantitatif. Metode deskriptif meliputi benchmarking, sedangkan pendekatan kuantitatif meliputi analisis marjin distribusi,  Data Envelopment Analysis (DEA), Analytic Hierarchy Process (AHP), dan analisis finansial. Hasil penelitian menunjukkan: 1) sistem distribusi “forwarder” adalah sistem distribusi yang digunakan oleh perusahaan, 2) Jawa Tengah termasuk kelompok “under-performing”, sedangkan Lampung dan Bali termasuk kelompok “effectively managed but sales”, 3) faktor kritis yang mempengaruhi tingginya biaya distribusi adalah jumlah distributor resmi yang dimiliki oleh perusahaan, 4) alternatif strategi terbaik adalah memperluas lokasi pemasaran di area produksi, dan 5) biaya investasi untuk membeli satu buah truk kontainer dapat dilakukan dengan Net B/C 4,88 selama lima tahun enam bulan. Strategi yang direkomendasikan adalah melalui pengembangan pasar, pemilihan transportasi dan jasa ekspedisi, kepemilikian distributor resmi, peningkatan penjualan, dan sistem manajemen yang terkoordinasi.Kata kunci: distribusi, marjin distribusi, DEA, AHP, analisis finansial